Putin's new National Guard: Bulwark against mass protests and illoyal elites - Margarete Klein (Stiftung Wissenschaft und Politik (SWP), 2016)
A new Russian security organ was created on 3 July 2016. The National Guard takes over the interior ministry's internal troops and police special forces and places them directly under the president's control. The new force's remit ranges from public order through counter-extremism and counter-terrorism to assistance in territorial defence and border protection. This reform represents the most significant restructuring of Russia's internal security organs in more than ten years, and exposes Putin's concerns over the robustness of his political system in face of persistent economic crisis and upcoming parliamentary and presidential elections. In this context the National Guard can serve not only as an instrument of repression against possible mass protests, but also as a means of disciplining potentially illoyal elite groups. (SWP Comments)
Keywords: 320